2013
DOI: 10.1124/mol.113.088864
|View full text |Cite
|
Sign up to set email alerts
|

Transnitrosylation Directs TRPA1 Selectivity in N-Nitrosamine Activators

Abstract: S-Nitrosylation, the addition of a nitrosyl group to cysteine thiols, regulates various protein functions to mediate nitric oxide (NO) bioactivity. Recent studies have demonstrated that selectivity in protein S-nitrosylation signaling pathways is conferred through transnitrosylation, a transfer of the NO group, between proteins via interaction. We previously demonstrated that sensitivity to activation by synthetic NO-releasing agents via S-nitrosylation is a common feature of members of the transient receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…A possible relationship between obesity and hypoferremia has recently been described in children [1,2,3] and women [4,5,6,7,8,9,10]. However, whether being overweight or obese is associated with increased risk of anemia or iron deficiency anemia (IDA) is still being debated [7,8,9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible relationship between obesity and hypoferremia has recently been described in children [1,2,3] and women [4,5,6,7,8,9,10]. However, whether being overweight or obese is associated with increased risk of anemia or iron deficiency anemia (IDA) is still being debated [7,8,9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, whether being overweight or obese is associated with increased risk of anemia or iron deficiency anemia (IDA) is still being debated [7,8,9,10,11,12,13,14]. Cheng and colleagues conducted a systematic review of 25 studies investigating iron status in obese populations and reported obese people tended to have higher hemoglobin (Hb) and ferritin concentrations, but lower transferrin saturation compared to non-obese controls [15].…”
Section: Introductionmentioning
confidence: 99%
“…Receptor-activated (TRPC5, TRPC1 and TRPC4) and thermosensor (TRPV1, TRPV3, TRPV4 and TRPA1) TRP channels are activated by exogenous NO-releasing donors through S -nitrosylation [ 29 , 32 ], but with very limited TRP subtype selectivity. Recently, this problem was partly solved with our finding that the 7-azabenzobicyclo[2.2.1]heptane (ABBH) N -nitrosamine selectively S -nitrosylates TRPA1 through transnitrosylation without releasing NO [ 76 ].…”
Section: Subtype Selective S -Nitrosylation By a Nmentioning
confidence: 99%
“…In contrast, the ABBH N -nitrosamines constitute a new class of NO donors that, at physiological pH and temperature, transnitrosylate thiols to generate S -nitrosothiols without releasing NO [ 150 - 152 ]. Surprisingly, our intracellular Ca 2+ imaging measurements have demonstrated that N -nitroso-2-exo,3-exo-ditrifluoromethyl-7-azabenzobicyclo [2.2.1] heptane (NNO-ABBH1) induces robust Ca 2+ influx via recombinant human TRPA1 channels, but not via other SNAP-activated TRP channels, suggesting that NNO-ABBH1 selectively S -nitrosylates TRPA1 [ 76 ] (Fig. 4 ).…”
Section: Subtype Selective S -Nitrosylation By a Nmentioning
confidence: 99%
See 1 more Smart Citation